In search of concepts: The effects of speculative demand on returns and volume - Owain Ap Gwilym; Qvigwei Wang; Iftekhar Hasan; Ru Xie (Bank of Finland, 2013)
Using a novel proxy of investors' speculative demand constructed from online search interest in "concept stocks", we examine how speculative demand affects the returns and trading volume of Chinese stock indices. We find that returns and trading volume increase with the contemporaneous speculative demand. In addition, the high speculative demand causes lower near future returns, while recent high past returns cause the high speculative demand. Moreover, the speculative demand explains more variation in returns and trading volume of A shares (more populated by retail investors) than B shares (less populated by retail investors). Our findings support the attention theory of Barber and Odean (2008).
URN:NBN:fi:bof-20140807364
Keywords: G02; G12; G14; 330; Investor Attention; Speculative Demand; Concept Stock; Market Returns; Trading Volume